Effects of Hazardous Waste on the Environment and Strategic Management Approaches (International Journal of Scientific Research in Science and Technology, 2026)
Hazardous waste has emerged as a significant global issue due to its detrimental impact on human health and the environment. Biomedical laboratories frequently handle hazardous and infectious materials, which contributes to the increasing presence of harmful substances in the ecosystem. These wastes encompass solid, liquid, sharp, and pathological materials. Workers in healthcare, agriculture, and fisheries are especially at risk of exposure to hazardous biological substances. Although the Government of India has recently implemented stricter and more systematic measures in response to public concern about hazardous waste production and unsafe disposal, effective waste management practices are still lacking. To avoid the build-up of biohazards in the environment, waste produced from hazardous activities must be treated and disposed of through specialized methods. This review also aims to raise awareness among personnel in relevant sectors and promote the development and implementation of effective hazardous waste management and mitigation strategies.